On the footprint of Kaniukas massacre - Zizas, Rimantas (Genocidas ir rezistencija, 2002)
In the armed conflict between the red army partisans and self–defenders of the villages of south–eastern Lithuania in 1943–1944, the attack on the village of Kaniūkai (Eišišiškės district, Jašiūnai municipality) on 29 January 1944 stands out as exceptional. The attack on Kaniūkai and the crackdown on the villagers is the most brutal punitive action of the red army partisans against the village self–defence, which turned into a bloodiest massacre (38 people were killed, almost the whole village was burnt to ashes). What were the circumstances, reasons, and motives behind the Kaniūkai attack? Why was the entire village so brutally reduced to ashes, and what were the reasons for the extraordinary cruelty of the red army partisans towards its residents?